Traditional vs Contemporary Dance in Cultural Preservation Across Southeast Asia: A Systematic Literature Review of Dance Arts Education (2019-2024) - Uthi Sonia; Indrayuda; Ardipal; Fuji Astuti (Journal for Lesson and Learning Studies, 2026)
The preservation of dance heritage across Southeast Asia is increasingly threatened by declining intergenerational transmission, yet no systematic framework has evaluated traditional and contemporary dance education approaches in tandem. This study aims to synthesize and evaluate the development of dance arts education across Southeast Asia during the 2019–2024 period, comparing traditional and contemporary approaches within the context of cultural preservation. A Systematic Literature Review following PRISMA 2020 guidelines was employed, with systematic searches across multiple databases and quality assessment using MMAT and AACODS. A total of 78 sources were included in the qualitative synthesis. Findings reveal that programs integrating contemporary pedagogies with traditional dance transmission prove more effective than those treating each approach in isolation. Technology serves as a preservation amplifier, and multi-stakeholder partnerships create more resilient transmission pathways. It can be concluded that the traditional-contemporary dichotomy is a false one, and the emerging framework of "adaptive authenticity" offers a novel model for sustainable dance education and cultural preservation.